Using the DigCompEdu Framework to analyse your institution’s support for teachers’ digital competencies development - Pedersen, Annette Q (Proceedings of the International Conference on Networked Learning, 2024)
Everyone agrees that teachers at all levels need to develop their digital competencies – but both the institution and the individual teachers need to take on this task – so this session asks: What can institutions do to take on some of the responsibility? Strategic goal setting is nice and helpful, but how can teaching and learning units, system owners and others improve the resources and help they provide to teachers to support digital competencies development? The University of Copenhagen have used the European framework DigCompEdu to analyse and evaluate how the university as an institution can better support the competence development needs of individual teachers. The purpose of this exercise was to avoid competence development becoming an individualized problem for the teacher. The participants have a choice in the workshop's hands-on part: Hands-on A: Plan an analysis of your own institution using the CUTE Canvas. Hands-on B: Analyse your own institution. This workshop is based on the work carried out in the ERASMUS+: Strategic Partnership CUTE (KA203-867FE04B) (2019-2022) and the CUTIE project (2022-2024)